Current and emerging biologics for the treatment of juvenile idiopathic arthritis. (2nd July 2020) - Cimaz, Rolando; Maioli, Gabriella; Calabrese, Giulia
ABSTRACT: Introduction: The management of a child with juvenile idiopathic arthritis (JIA) requires a combination of pharmacological, physical, and psychosocial therapies in order to induce disease remission, by controlling articular and systemic inflammation. This review aims to provide a comprehensive discussion on the biological therapies currently in use in the treatment of JIA referring to existing recommendations and clinical evidence. We also discuss on the emerging biological drugs actually under consideration. Areas covered: Recent findings on immunological mechanisms involved in the pathogenesis of the disease allowed us to identify several specific targets for biologic therapies. A systematic literature review was conducted between January 1997 and January 2020 on PubMed including national and international guidelines and recommendations, trials and case–control studies. Expert opinion: There is now a plethora of therapies that are directed against variable targets, and the physician has to choose the most appropriate available medication in order to achieve early and sustained remission with as few side effects as possible. Research is advancing very fast in order to be more and more specific in suppressing inflammatory pathways without harming natural defenses. Finally, pharmacoeconomic considerations will also be very important to deal with, considering the high cost of most of these molecules.